Cenozoic tectonic evolution of southeastern thailand derived from low-temperature thermochronology - Simon Nachtergaele (2020)
© 2019 The Author(s). Low-temperature thermochronological techniques, specifically apatite (U–Th)/He and apatite fission-track dating, were used to reconstruct the thermal history of southeastern Thailand. This area is intersected by vast and complex fault networks related to the Cenozoic Mae Ping and Three Pagodas Faults. These were identified from satellite imagery and confirmed by field observations. New apatite fission-track and apatite (U–Th)/He data were collected from crystalline basement blocks within these fault networks. Ages obtained range from 48 to 24 Ma, with most of the samples clustering between 36 and 24 Ma. Thermal history modelling indicates late Eocene–Oligocene exhumation of the exposed granitic and metamorphic basement rocks in southeastern Thailand. Exhumation was regional and was contemporaneous with sinistral fault activity during the late Eocene–early Oligocene along the Mae Ping Fault and Three Pagodas Fault. Moreover, this exhumation occurred coevally with a synrift phase of intracontinental offshore rift basin and half-graben basin development in the eastern Gulf of Thailand. The phase of exhumation ended in the early Miocene, as a result of the changing plate-tectonic forces along the complex plate boundaries of Sundaland.